Pengaruh Atribut Produk terhadap Pengambilan Keputusan Konsumen dalam Pembelian Produk Sabun Mandi - Sarifa Amnah; Mulyadi Mulyadi; Mutawali Hasan (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2020)
The purpose of this study was to determine the effect of product attributes on consumer decision making in purchasing bath soap products. The data collection method used survey sample, the sampling used was simple random sampling with housewives as respondents. The number of respondents in this study were 100 people. Data analysis in this study was carried out with two approaches, namely qualitative analysis and quantitative analysis, qualitative analysis using the scoring method which refers to the Likert scale used to measure attitudes, opinions and perceptions of a person or group about social phenomena. Meanwhile, the quantitative analysis used non-parametric statistical analysis tools, namely the chi square (x2) analysis tool used to determine the presence or absence and strength of the effect of product attributes (quality, brand, packaging, label) on soap. The results showed that the attributes of quality, brand and packaging had a significant influence on consumer decisions in choosing a soap brand. For the quality attribute of the chi square the count is 31.96 with the chi table of 9.49.The chi square brand attribute is 21.29 with the chi square table 9.49 for the attribute of the chi square package the count is 9.88 with the chi table of 9.49 The tributary of the chi square label is 4.40 with the chi table of 9.49. Of the four variable product attributes, the one that has the strongest influence is the quality attribute, because the chi square count is the highest, the next influence is Brand, Packaging